Rapid Detection of Virulence Genes in Vibrio cholerae from Edible Ice in Jakarta - DIANA E. WATURANGI; MARISA FRANSISCA (Microbiology Indonesia, 2009)
Vibrio cholerae is a bacteria that lives naturally in an aquatic environment. It causes a waterborne disease which is called cholera. Infection of waterborne disease occurs via the fecal-oral route, mostly through drinking water. As we know, ice is made from city water sources and it is commonly used in beverages. Most of publications about V.cholerae come from clinical samples, while little is known about the presence of these bacteria in potable water, especially in ice. In this study, we isolated V. cholerae from ice in Jakarta and continued with detection of the virulence genes. We recovered V. cholerae from ice samples and then continued with detection of virulence genes including toxR, ctxA, ompU, tcpA, ace, zot using multiplex PCR. The results indicated that all of the samples were non-toxigenic strains, but were classified as pathogenic strains because they have at least one of the virulence genes present. The presence of pathogenic V. cholerae in edible ice needs to be emphasized since they have some of the virulence factors and also the class 1 integron.